The Significance of Comprehensive Sexual Education in Preventing Adolescent Sexual Misconduct - Karimullah, Suud Sarim (IAIN Syekh Nurjati Cirebon, 2023)
ABSTRACT: This study explores the urgency of comprehensive sexual education as a critical solution to the problem of sexual delinquency in adolescents. To gain an in-depth understanding of the importance of comprehensive sexual education in the Prevention of sexual delinquency in adolescents, this review applies an integrative and comprehensive literature analysis approach in reviewing various sources and related studies covering critical aspects of this topic. The results of the study stated that comprehensive sexual education is not just an option but a vital necessity in maintaining the well-being and future of the younger generation. In addition, sexual education also plays a role in shaping a culture that respects individual rights, promotes positive sexual health values, and creates a society that is more inclusive and concerned about sexuality issues. Thus, comprehensive sexual education becomes an indispensable part of efforts to protect adolescents and ensure that they can grow and develop healthily and responsibly in terms of their sexuality.Keywords: Comprehensive Sexual Education; Sexual Behavior; Youth Sexual Behavior.